A Criminological Analysis and Preventive Approaches: The Risk Conditions and Crimes on Dating Applications among LGBTQ+ in Thai Society - Dommongkol, Phimakorn (Arts of Management Journal, 2026)
This academic article aims to study risk conditions, crime patterns, criminological analysis, and propose preventive measures for crimes arising from the use of dating applications among LGBTQ+ individuals. The methodology is a systematic literature review of secondary data from 2020–2024, combined with three theoretical frameworks: General Strain Theory, Social Process Theory, and Crime Prevention Through Environmental Design (CPTED). The findings identify significant risk behaviors including HIV, sex addiction, chemsex (drug use during sex), text neck syndrome from prolonged use, and digital eye strain. Crimes are categorized as child and youth sexual abuse, violence against life and property, online drug networks, covert prostitution and sexual service platforms, and crimes in public spaces. The analysis indicates that these deviant behaviors are rooted in micro-level stress, peer influence, and the absence of capable guardians in meeting places. The article proposes a four-level integrated prevention approach: individual, family, society/community, and government, to create a safe digital environment and sustainably uphold the human dignity of LGBTQ+ people in Thai society.